PENGARUH NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM DENGAN RETURN ON ASSET SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI SEKTOR INDUSTRI ROKOK Periode 2011 – 2015 - ABDALLAH, ZACHARI (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2018)
ABSTRACT This research has purpose to know influence of rupiah exchange rate to stock return with roa as intervening variable. The type of research used is quantitative research with descriptive method. Secondary date used in this research are financial statement of manufacturing company in cigarette industry sector registered in period 2011 – 2015 period. Date analysis with population of 4 companies and sample size of 3 companies from population. The analysis result of this research is rupiah exchange rate does not influence partially to stock return, but if using roa as intervening variable hence existence of direct and indirect influence between rupiah exchange rate to stock return. Keyword : Rupiah Exchange Rate, Stock Returns, Return On Asset (ROA)